2002
DOI: 10.1080/152873902753396785
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Blood Mercury and Neuro-Otological Observations in Children of the Ecuadorian Gold Mines

Abstract: The prevalence of mercury (Hg) intoxication was investigated in 114 Andean Saraguro and non-Saraguro (Mestizo) children living in remote gold-mining settlements in Nambija and Portovelo, Ecuador. Venous blood samples showed a mean total blood mercury (B-Hg) level of 18.2 microg/L (SD 15.5; range 2-89.) for 77 Saraguro and non-Saraguro children in the Nambija settlement, which was significantly higher than that of children in the Portovelo and reference groups. Comparison of groups showed mean B-Hg levels of 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 30 publications
0
47
0
1
Order By: Relevance
“…Most of the gold mining in Ecuador is concentrated in the southern Sierra, although one region in the Andes on the oriental side is involved in this practice. Studies in this region, roughly 400 km and several catchments away from the Napo River Valley, have shown that soils, stream sediments, and mine tailings are contaminated by metallic Hg (Ramírez Requelme et al, 2003), that blood Hg levels are high in local populations (Counter et al, 1998(Counter et al, , 2002, that children are at risk for neurodevelopmental disabilities (Counter, 2003), and that auditory neurosensory capacities are diminished in the exposed population (Counter et al, 1998(Counter et al, , 2002. The extensive petroleum extraction taking place in the Northern Ecuadorian Amazon could also be contributing to mercury loads though the discharge of toxic wastes, numerous spills, and the burning of excess gas (Kimerling, 1993;IESC, 2000).…”
Section: Introductionmentioning
confidence: 98%
“…Most of the gold mining in Ecuador is concentrated in the southern Sierra, although one region in the Andes on the oriental side is involved in this practice. Studies in this region, roughly 400 km and several catchments away from the Napo River Valley, have shown that soils, stream sediments, and mine tailings are contaminated by metallic Hg (Ramírez Requelme et al, 2003), that blood Hg levels are high in local populations (Counter et al, 1998(Counter et al, , 2002, that children are at risk for neurodevelopmental disabilities (Counter, 2003), and that auditory neurosensory capacities are diminished in the exposed population (Counter et al, 1998(Counter et al, , 2002. The extensive petroleum extraction taking place in the Northern Ecuadorian Amazon could also be contributing to mercury loads though the discharge of toxic wastes, numerous spills, and the burning of excess gas (Kimerling, 1993;IESC, 2000).…”
Section: Introductionmentioning
confidence: 98%
“…While genetic factors are recognized as being important in the pathogenesis of ASDs, a role for environmental factors has received considerable attention. Several recent epidemiological studies have associated mercury exposure with ASDs (Counter et al, 2002;Holmes et al, 2003;Geier and Geier, 2005;Palmer et al, 2006;Windham et al, in press), and it has been reported that exposure to mercury can cause immune, sensory, neurological, motor, and behavioral dysfunctions similar to traits defining or associated with ASDs, and that these similarities extend to neuroanatomy, neurotransmitters, and biochemistry (Faustman et al, 2000;Bernard et al, 2001;Redwood et al, 2001;Blaxill et al, 2004). Furthermore, a recent review has suggested that ASD children have been found to have significantly higher exposure to mercury than controls, and ASD children have been determined to have significantly increased body-burdens of mercury resulting from biochemical and genomic susceptibilities within detoxification pathways (Mutter et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, 10-15 million artisanal gold miners in more than 70 countries extract on average 350 tonnes/ a of gold, and in the process, release 640-1350 tonnes/a of mercury into the environment [3]. While the use of mercury in the amalgamation process of gold mining is considered a global problem affecting the environment and human health [4][5][6][7], scientists' limited knowledge about its discharge pathways reduces the development of solutions to identifying ways in which to eliminate or reduce emissions. Key information about quantification of the mercury emissions from processing sites as well as the distribution of the mercury throughout effluents is badly needed [8].…”
Section: Introductionmentioning
confidence: 99%